DESAIN ANTENA MIKROSTRIP RECTANGULAR UNTUK APLIKASI RADAR ALTIMETER - Dhimas Annas Saputro (Approach : Jurnal Teknologi Penerbangan, 2021)
Antenna is one of the vital components in a transmitter or receiver. Antennas work by transmitting and receiving electromagnetic waves to and from the air. Microstrip antenna is one type of antenna that is currently often applied in several equipment as an alternative antenna and antenna innovation due to the easy and cheap fabrication process. A radar altimeter is a device used to measure the altitude or vertical distance from an airplane to the ground or to the sea level. Antenna is an important component in a radar altimeter which functions to transmit radio waves and receive radio waves either at the same frequency or in a frequency range. In this study, a rectangular microstrip antenna for radar altimeter was designed that operates at a working frequency of 4200 - 4300 GHz using the CST Studio Suite 2019 software as a form of alternative antenna learning media at a frequency of 4200 - 4300 GHz and is expected to have a VSWR â‰¤2 parameter value. and the return loss value â‰¤ 10 dB